Synthesis of Boranoate, Selenoate, and Thioate Analogs of AZTp(4)A and Ap(4)A - Han, Qianwei (2009)
We report efficient, one-flask procedures for the synthesis of a family of fourteen analogs of AZTp(4)A and Ap(4)A containing BH(3), S, or Se, along with two bisphosphonate analogs of Ap(4)A. These compounds should slow unwanted enzymatic hydrolysis and have the potential to create unique binding interactions in biochemical and structural studies of the excision reaction responsible for resistance of HIV-1 to AZT, as well as assist in drug design.